ORRELATION BETWEEN LIFE EXPECTANCY AND PERCENTAGE POPULATION OVER 65 YEARS - Teguh Widodo, Indang Dewata, Iswandi Umar, Ramadhani (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Life expectancy is not only one of the health indicators but also as a component to determine the human development index. Unfortunately, it is not relevant anymore as it in current condition because many people suffer from degenerative diseases so that they pass away in productive age. Currently, the infant mortality rate (IMR) and maternal mortality rate (MMR) as prominent factors in determining life expectancy tend to decrease because those factors are more caused by lack of accessibility to the health facilities such as medical centre, devices and officers. To prove that statement, it is examined by linear regression between life expectancy and percentage population over 65 years. The result shows that there are no correlations of both. Finally, this research recommends shifting life expectancy by the percentage of the population over 65 years as a key indicator in health status.